Analisis Sistem Ventilasi Tambang Batubara Bawah Tanah Untuk Kebutuhan Operasional Penambangan Pada Lubang Tambang C.2-I Job Site Sapan Dalam PT. Nusa Alam Lestari Parambahan Kota Sawahlunto - Insani Sabilillah; Bambang Heriyadi; Jukepsa Andas; Refky Adi Nata (Journals Mining Engineering : Bina Tambang, 2023)
PT. Nusa Alam Lestari is an underground coal mining company located in Salak Village, Talawi District, Sawahlunto City, West Sumatra. Ventilation system at mine pit C.2-I Job Site Sapan Dalam PT. Nusa Alam Lestari uses a blow system. This study aims to evaluate the quality and quantity of ventilation systems for underground coal mines in accordance with the Decree of the Minister of Energy and Mineral Resources No. 1827 K/30/MEM/2018 and Decree of the Director General of Minerba and ESDM No. 185 K/37.04/DJB/2019 with parameters which include gas content, relative humidity, effective temperature value, work efficiency value and air quantity for mining operational needs. At mine pit C.2-I there is an advanced front and six mining branches. The average temperature measurement results in the working front of the C.2-I mine pit are 29.6oC and with an average humidity measurement result of 94.6%. This temperature value has passed the set threshold between 18oC - 27oC and the humidity has also passed the set threshold, which is 85%. In addition, the C.2-I mine pit does not apply a suction ventilation system, so that dirty air is not immediately transported out. The ventilation system applied to the C.2-I mine pit can only meet 70% of the air demand, so it is necessary to evaluate and design a new ventilation system. The design of the ventilation system is carried out by making a tail gate from the Cross Cut to the surface with an elevation of 15o with a length of 170 m. The end of the through hole is given an 18 inch Centrifugal Exhaust Fan, to suck in dust and dirty air. Making mining layouts using AutoCAD and design simulations using the Ventsim program. The results of the analysis show that the quantity of air in the C.2-I mine hole has increased from 4.08 m3/s to 7.38 m3/s. The design of the new ventilation system results in compliance with the values of air quality and quantity.